Intensive Care Unit Services Preparedness for the Pandemic: An Efficiency Analysis...47th annual meeting (online) of the EURO Working Group on Operational Research Applied to Health Services: July 5-9, 2021. - Cinaroglu, Songul (Health Services Insights, 2021)
Intensive care unit (ICU) services efficiency and the shortage of critical care professionals has been a challenge during pandemic. Thus, preparing ICUs is a prominent part of any pandemic response. The objective of this study is to examine the efficiencies of ICU services in Turkey right before the pandemic. Data were gathered from the Public Hospital Statistical Year Book for the year 2017. Analysis are presented at hospital level by comparing teaching and non-teaching hospitals. Bootstrapped data envelopment analysis procedure was used to gather more precise efficiency scores. Three analysis levels are incorporated into the study such as, all public hospitals (N = 100), teaching (N = 53), non-teaching hospitals (N = 47), and provinces that are providing high density of ICU services through the country (N = 54). Study results reveal that average efficiency scores of ICU services obtained from teaching hospitals (eff = 0.65) is higher than non-teaching (eff = 0.54) hospitals. After applying the bootstrapping techniques, efficiency scores are significantly improved and the difference between before and after bootstrapping results are statistically significant (P <.05). Province based analysis indicates that, ICU services efficiencies are high for provinces located in southeast part of the country and highly populated places, such as İstanbul. Evidence-based operational design that considers the spatial distribution of health resources and effective planning of critical care professionals are critical for efficient management of intensive care. Study results will be helpful for health policy makers to deeply understand dynamics of critical care.